2012
DOI: 10.1007/s10753-012-9538-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Inflammatory and Oxidative Biomarkers in Obesity and Their Associations with Body Mass Index

Abstract: The aim of this study was to evaluate the inflammatory and oxidative biomarkers' levels in obese subjects and their associations with body mass index (BMI), in order to investigate the role of these biomarkers in obesity. Fasting glucose, total cholesterol, HDL cholesterol, LDL cholesterol, triglycerides, apolipoprotein A, apolipoprotein B, albumin, urinary albumin, creatinine, glomerular filtration rate, interleukin-6 (IL-6), nitrate/nitrite (NOx), and ischemia-modified albumin (IMA) were measured in 93 subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 33 publications
0
35
1
1
Order By: Relevance
“…The elevation observed in this study parallels studies in humans, indicating a consistency in the inflammatory response to obesity between humans and dogs, yet the rise is not as robust as observed in human studies (Fried et al, 1998;Bastard et al, 2002;Piva et al, 2013). Some have hypothesized that in absence of acute inflammation, fifteen to thirty percent of circulating IL-6 levels comes from adipose tissue, including the macrophages and stromal cells contained within the tissue (Mohamed-Ali et al, 1997).…”
Section: Discussioncontrasting
confidence: 42%
See 3 more Smart Citations
“…The elevation observed in this study parallels studies in humans, indicating a consistency in the inflammatory response to obesity between humans and dogs, yet the rise is not as robust as observed in human studies (Fried et al, 1998;Bastard et al, 2002;Piva et al, 2013). Some have hypothesized that in absence of acute inflammation, fifteen to thirty percent of circulating IL-6 levels comes from adipose tissue, including the macrophages and stromal cells contained within the tissue (Mohamed-Ali et al, 1997).…”
Section: Discussioncontrasting
confidence: 42%
“…However, in these studies many of the samples were near the lower limit of detection. Based on the changes observed in IL-6 in this study the elevation would be considered minimal compared to human studies (Piva et al, 2013), therefore the population necessary in these previous studies may have been inadequate to find significant elevations in serum IL-6. In fact, considering the trends of elevations due to obesity in humans with typically larger populations our power analysis may have been inadequate to observe differences in some of the cytokines such as IL-2, IL-10 and IL-8, which never reached statistical significance, but might be considered interesting trends that warrant further research with larger populations of dogs.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…These subjects exhibited IMA production. Another suggestion from the study was that alterations in inflammatory and oxidative stress biomarkers in obese subjects can be indicated by diabetes, which is a dependent predictor, according to an advanced statistical analysis on BMI (33). Regarding these results, it was concluded that the oxidative stress condition must be increased by a comorbidity, as IMA levels cannot increase merely due to obesity.…”
Section: Discussionmentioning
confidence: 96%